Polygonatum polysaccharide modified montmorillonite/chitosan/glycerophosphate composite hydrogel for bone tissue engineering. Issue 15 (13th October 2022) - Zhao, Xiaoliang; Li, Pingping; Zhu, Jianning; Xia, Yunya; Ma, Jianzhong; Pu, Xiuying; Wang, Yonggang; Leng, Feifan; Wang, Yanling; Yang, Shuhong; Ran, Fen; Tang, Dan; et al.
Abstract: The stiffness and gelation temperature of thermo-responsive chitosan (CS), glycerophosphate (GP) hydrogel is not enough for differentiation of BMSCs and injecting use in bone defect repair. To improve these weaknesses, a kind of injectable hydrogel (PMCG) was prepared with Chitosan (CS), glycerophosphate (GP), polygonatum polysaccharide modified montmorillonite (PMMT). The gelation temperature of CS/GP (CG) hydrogel was 42 °C, the maximum mechanical strength was 1061 Pa. with the amount of PMMT increased, the gelation temperature decreased to 28 °C, and the maximum stiffness increased to 6789 Pa. At the same time, with the addition of PMMT, the swelling property of hydrogel was improved. The cytocompatibility of PMCG decreased than CG which maybe result from the poor cytocompatibility of montmorillonite, but it was improved with increasing amount of PMMT, which indicated the cell proliferation promoting effect coming from polygonatum polysaccharide. The SEM-EDX exhibited that these hydrogels possessed excellent morphological characteristics and could promote mineralization in simulated body fluid (SBF) solution, PMCG-2 Ca/P has a Ca/P ratio of 1.63 ± 0.04, which is similar to the ratio of human bone mineral (Ca/P ratio of 1.55–1.75). The cell viability confirmed the application availability of the hydrogel. In light of the effect on osteoblasts maturation promoting effect and decrease of osteoclast of polygonatum polysaccharide. We come to the conclusion that it is an effective strategy to improve the mechanic strength and gelation temperature, and keep the osteogenesis promoting effect at the same time. Graphical Abstract: UF0001